PKM Perawatan dan Perbaikan Alat-Alat Rumah Tangga Listrik Untuk Mengatasi Dampak Covid-19 di Kab. Gowa - Muliadi Muliadi; Alifya NFH (DEDIKASI, 2020)
This community service activity aims to provide training on maintenance and repair of electrical and electronic equipment for households to the Child Social Welfare Institution (LKSA) in Kalegowa Subdistrict, Somba Opu District, Gowa Regency which is a partner of the activity. The methods used in this service were: lectures, questions and answers, discussions and demonstration methods were used for training. The solution taken in solving partner problems, namely training activities for maintenance and repair of household electrical appliances based on project work is carried out to provide knowledge about basic concepts of electricity and electronics, basic electronic components, and repair of electrical household appliances. The results achieved in this service activity are 10 foster children of productive age from partners who are skilled and competent in repairing electrical household appliances, have knowledge of how to use electric and electronic measuring instruments, how to use electrical and electronic equipment, workshop management, K3, and entrepreneurship